Comparative Study of Figurative Language Used in Adventure Video Game and MOBA Video Game - Rahimi, Rahmat Randi; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
Figurative language is a way of uttering or writing words by setting aside their literal form and replacing them with other words that describe the intended meaning. In this research, the researcher aimed to analyze the types of figurative language and cultural ambiguities used in Genshin Impact, Ghost of Tsushima, Arena of Valor, and Honor of Kings. This study used a descriptive qualitative method to collect the data. The researcher analyzed the utterances containing figurative language and examined any instances of cultural ambiguity. The researcher identified all the utterances that demonstrated types of figurative language and cultural ambiguity. The study determined the types of figurative language and cultural ambiguity employed in those video games. As a result, the researcher found 36 data of types of figurative language. There are 19 data of personification utterances, 5 data of metaphor occurrences, 3 data of simile sentences, 3 examples of hyperbole, 3 sentences containing paradox, 1 data of synecdoche utterance, 1 example of understatement, and 1 instance of antithesis. Additionally, the researcher found 21 data of types of cultural ambiguity. There are 11 instances of semantic ambiguity, 7 data of referential ambiguity sentences, and 3 data of pragmatic ambiguity utterances. Genshin Impact and Ghost of Tsushima were categorized as adventure games, while Arena of Valor and Honor of Kings were classified as MOBA video games. The study found that adventure video games used hyperbole, synecdoche, and understatement. Meanwhile, MOBA video games preferred personification, metaphor, simile, paradox, and antithesis.